Policy implementation and public satisfaction index concerning COVID-19 pandemic handling in East Lombok Regency - Rosidi, Ahyar; Kumboyono, Kumboyono; Srihayati, Yati (International Journal of Public Health Science (IJPHS), 2023)
The 2019's coronavirus disease is an infectious illness brought on by the SARS-CoV-2 coronavirus. Compliance with health protocols by the public is declining. Physical distance-keeping is no longer common in public spaces, and many people no longer wear masks when leaving the house. The populace feels that specific areas, such as schools, campuses, and places of worship, are the only ones under surveillance and supervision. Federal, state, and local governments have set up rules to prevent the spread of the disease. This study employs quantitative survey research techniques. The researchers used surveys on policy execution and a public satisfaction score. The Spearman rank and multiple linear regression tests were employed in the data analysis for this investigation. There were 300 respondents who filled out a questionnaire followed by data analysis. The results of data analysis using the Spearman rank test obtained a p-value of 0.000<0.05 with a Spearman correlation value of 0.26. The p-value for handling is 0.000<0.05 with a Spearman correlation value of 0.232. The multiple linear regression test resulted in a COVID-19 prevention policy by adding a community satisfaction index of 21.8% and a COVID-19 handling policy by adding a community satisfaction index of 15.7%.